Apparel retailing business in selected Iloilo City malls surviving the economic crisis - Dionela, Bernadette; Go, Alvin; Java, Joanne; Lacay, Gretchen; Lecias, Mary Gene.
It was the desire of the proponents to find out the coping mechanisms of apparel retailing stores in order to survive during the period of economic turmoil. based on the interview conducted, findings and results clearly showed that the economic crises affected the operating performance of apparel retail stores located in selected malls. Such affects however did not bring significant changes particularly the strategies employed by the apparel stores. Though affected by the crises, they did not employ new strategies and exert extra efforts in response to such crises. Since the degree of the effect of the economic turmoil is not that strong, it did not impel them to think of new strategies and techniques. The strategies implemented during the time of crises ae the same they used before.
[Research Paper] (BA 200 - Business Research) -- [Iloilo City] : UPV-CM, [n.d.]